2002
DOI: 10.1016/s0034-4257(02)00027-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimating fire-related parameters in boreal forest using SPOT VEGETATION

Abstract: The majority of burning in the boreal forest zone consists of stand replacement fires larger than 10 km 2 occurring in remote, sparsely populated regions. Satellite remote sensing using coarse resolution ( c 1 km) sensors is thus well suited in documenting the spatial and temporal distribution of fires in this zone. The purpose of this study was to investigate the utility of the SPOT VEGETATION (VGT) sensor for estimating three key parameters related to boreal forest fire: burned area, postfire regeneration ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 48 publications
5
53
0
1
Order By: Relevance
“…It supports the findings of previous studies that the NIR provides high burned-unburned discrimination in a variety of ecosystems including, for example, boreal forest [23,78,79], savanna [23,75,80] and temperate forest [36]. As observed in other studies, the visible bands provide low burned-unburned discrimination [23,75,81,82].…”
Section: Discussionsupporting
confidence: 91%
“…It supports the findings of previous studies that the NIR provides high burned-unburned discrimination in a variety of ecosystems including, for example, boreal forest [23,78,79], savanna [23,75,80] and temperate forest [36]. As observed in other studies, the visible bands provide low burned-unburned discrimination [23,75,81,82].…”
Section: Discussionsupporting
confidence: 91%
“…The NBR exhibits a large drop after burning, owing to the removal of leafy vegetation, which decreases NIR scattering, SWIR water absorption and canopy shadowing [22,45]. In this study, we similarly found that dNBR was effective for predicting CBI (Table 4), but also demonstrated that Landsat indices were even more closely related to specific indicators of burn severity derived from UAV mapping (Figure 4).…”
Section: Discussionsupporting
confidence: 61%
“…It reflects surface canopy moisture and forest humidity [55,56]. The NDWI has been used for monitoring water stress [57], and for mapping burnt areas in boreal forest [58]. Thus, the changing pattern of the NDWI with the seasons could distinguish areas of natural vegetation, farmland, and soil, in relation to moisture.…”
Section: Normalized Indicesmentioning
confidence: 99%